2.2.130 Problems 12901 to 13000

Table 2.261: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

12901

\[ {}y^{2} \left ({y^{\prime }}^{2}+1\right ) = a^{2} \]

[_quadrature]

4.460

12902

\[ {}y y^{\prime } = \left (x -b \right ) {y^{\prime }}^{2}+a \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

0.542

12903

\[ {}x^{3} {y^{\prime }}^{2}+x^{2} y y^{\prime }+1 = 0 \]

[[_homogeneous, ‘class G‘], _rational]

4.601

12904

\[ {}3 x {y^{\prime }}^{2}-6 y y^{\prime }+x +2 y = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

2.436

12905

\[ {}y = {y^{\prime }}^{2} \left (x +1\right ) \]

[[_homogeneous, ‘class C‘], _rational, _dAlembert]

0.717

12906

\[ {}\left (-y+y^{\prime } x \right ) \left (x +y y^{\prime }\right ) = a^{2} y^{\prime } \]

[_rational]

117.895

12907

\[ {}{y^{\prime }}^{2}+2 y^{\prime } y \cot \left (x \right ) = y^{2} \]

[_separable]

1.081

12908

\[ {}\left (x^{2}+1\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2}-1 = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

0.553

12909

\[ {}x^{2} {y^{\prime }}^{2}-2 \left (x y+2 y^{\prime }\right ) y^{\prime }+y^{2} = 0 \]

[_separable]

3.414

12910

\[ {}y = y^{\prime } x +\frac {y {y^{\prime }}^{2}}{x^{2}} \]

[[_1st_order, _with_linear_symmetries]]

3.074

12911

\[ {}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2} = x^{2} y^{2}+x^{4} \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

9.378

12912

\[ {}y = y^{\prime } x +\frac {1}{y^{\prime }} \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

0.362

12913

\[ {}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

1.328

12914

\[ {}x^{2} {y^{\prime }}^{2}-2 \left (x y-2\right ) y^{\prime }+y^{2} = 0 \]

[[_homogeneous, ‘class G‘], _Clairaut]

0.559

12915

\[ {}x^{2} {y^{\prime }}^{2}-\left (x -1\right )^{2} = 0 \]

[_quadrature]

1.002

12916

\[ {}8 \left (1+y^{\prime }\right )^{3} = 27 \left (x +y\right ) \left (1-y^{\prime }\right )^{3} \]

[[_homogeneous, ‘class C‘], _dAlembert]

30.420

12917

\[ {}4 {y^{\prime }}^{2} = 9 x \]

[_quadrature]

0.251

12918

\[ {}y \left (3-4 y\right )^{2} {y^{\prime }}^{2} = 4-4 y \]

[_quadrature]

11.697

12919

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

[[_2nd_order, _missing_x]]

1.074

12920

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

[[_2nd_order, _missing_x]]

2.046

12921

\[ {}y^{\prime \prime \prime }-y^{\prime } = 0 \]

[[_3rd_order, _missing_x]]

0.064

12922

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0 \]

[[_3rd_order, _missing_x]]

0.071

12923

\[ {}4 y^{\prime \prime \prime }-3 y^{\prime }+y = 0 \]

[[_3rd_order, _missing_x]]

0.071

12924

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime }+y = 0 \]

[[_3rd_order, _missing_x]]

0.070

12925

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime }-y = 0 \]

[[_high_order, _missing_x]]

0.075

12926

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+9 y^{\prime } = 0 \]

[[_3rd_order, _missing_x]]

0.069

12927

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = 0 \]

[[_high_order, _missing_x]]

0.085

12928

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime } = 0 \]

[[_3rd_order, _missing_x]]

0.073

12929

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }-2 y^{\prime } = {\mathrm e}^{-x} \]

[[_3rd_order, _missing_y]]

0.112

12930

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{{\mathrm e}^{x}} \]

[[_2nd_order, _linear, _nonhomogeneous]]

1.326

12931

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = 2 \,{\mathrm e}^{-x}-x^{2} {\mathrm e}^{-x} \]

[[_3rd_order, _linear, _nonhomogeneous]]

0.164

12932

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{\left (1-x \right )^{2}} \]

[[_2nd_order, _linear, _nonhomogeneous]]

0.868

12933

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{x} \]

[[_2nd_order, _with_linear_symmetries]]

1.240

12934

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }-y^{\prime }+3 y = x^{2} \]

[[_3rd_order, _with_linear_symmetries]]

0.152

12935

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

[[_2nd_order, _linear, _nonhomogeneous]]

2.932

12936

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime }+5 y^{\prime }-2 y = x \]

[[_3rd_order, _with_linear_symmetries]]

0.115

12937

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

[[_2nd_order, _linear, _nonhomogeneous]]

2.852

12938

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

[[_2nd_order, _linear, _nonhomogeneous]]

3.131

12939

\[ {}y^{\prime \prime }+4 y = x^{2}+\cos \left (x \right ) \]

[[_2nd_order, _linear, _nonhomogeneous]]

4.599

12940

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 2 x \,{\mathrm e}^{2 x}-\sin \left (x \right )^{2} \]

[[_2nd_order, _linear, _nonhomogeneous]]

3.802

12941

\[ {}y^{\prime \prime }+y = 2 \,{\mathrm e}^{x}+x^{3}-x \]

[[_2nd_order, _linear, _nonhomogeneous]]

2.411

12942

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 3 \,{\mathrm e}^{2 x}-\cos \left (x \right ) \]

[[_2nd_order, _linear, _nonhomogeneous]]

1.931

12943

\[ {}y^{\prime \prime \prime }-y = x^{2} \]

[[_3rd_order, _with_linear_symmetries]]

0.120

12944

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-3 y^{\prime } = 3 x^{2}+\sin \left (x \right ) \]

[[_3rd_order, _missing_y]]

0.188

12945

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y = {\mathrm e}^{x}+4 \]

[[_high_order, _with_linear_symmetries]]

0.138

12946

\[ {}y^{\prime \prime }-2 y^{\prime } = {\mathrm e}^{2 x}+1 \]

[[_2nd_order, _missing_y]]

2.185

12947

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = \cos \left (x \right ) \]

[[_high_order, _linear, _nonhomogeneous]]

1.012

12948

\[ {}x^{3} y^{\prime \prime \prime }+y^{\prime } x -y = x \ln \left (x \right ) \]

[[_3rd_order, _with_linear_symmetries]]

0.256

12949

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }+2 y = 10 x +\frac {10}{x} \]

[[_3rd_order, _exact, _linear, _nonhomogeneous]]

0.750

12950

\[ {}x^{2} y^{\prime \prime }+3 y^{\prime } x +y = \frac {1}{\left (1-x \right )^{2}} \]

[[_2nd_order, _exact, _linear, _nonhomogeneous]]

1.846

12951

\[ {}\left (x +1\right )^{2} y^{\prime \prime }-\left (x +1\right ) y^{\prime }+6 y = x \]

[[_2nd_order, _with_linear_symmetries]]

16.716

12952

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = \cos \left (x \right )-{\mathrm e}^{2 x} \]

[[_2nd_order, _linear, _nonhomogeneous]]

2.046

12953

\[ {}y^{\prime \prime \prime \prime }-y = {\mathrm e}^{x} \cos \left (x \right ) \]

[[_high_order, _linear, _nonhomogeneous]]

0.137

12954

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 x^{3}-x \,{\mathrm e}^{3 x} \]

[[_2nd_order, _linear, _nonhomogeneous]]

1.538

12955

\[ {}y^{\prime \prime \prime }-4 y^{\prime } = x^{2}-3 \,{\mathrm e}^{2 x} \]

[[_3rd_order, _missing_y]]

0.144

12956

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y = \cos \left (x \right ) \]

[[_high_order, _linear, _nonhomogeneous]]

0.138

12957

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+9 x^{2} y^{\prime \prime }+3 y^{\prime } x +y = \left (1+\ln \left (x \right )\right )^{2} \]

[[_high_order, _linear, _nonhomogeneous]]

0.832

12958

\[ {}y^{\prime \prime \prime }+2 y^{\prime \prime }+y^{\prime } = x^{2}-x \]

[[_3rd_order, _missing_y]]

0.128

12959

\[ {}y^{\prime \prime }+4 y = \sin \left (x \right )^{2} \]

[[_2nd_order, _linear, _nonhomogeneous]]

4.413

12960

\[ {}y^{\prime \prime }+4 y = \sec \left (x \right )^{2} \]

[[_2nd_order, _linear, _nonhomogeneous]]

4.793

12961

\[ {}y^{\prime \prime \prime \prime }-y^{\prime \prime \prime }-3 y^{\prime \prime }+5 y^{\prime }-2 y = {\mathrm e}^{3 x} \]

[[_high_order, _with_linear_symmetries]]

0.122

12962

\[ {}y^{\prime \prime }+y = x \cos \left (x \right ) \]

[[_2nd_order, _linear, _nonhomogeneous]]

3.621

12963

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-y^{\prime } x +y = \frac {1}{x} \]

[[_3rd_order, _exact, _linear, _nonhomogeneous]]

0.250

12964

\[ {}y^{\prime \prime \prime }-y = x \,{\mathrm e}^{x}+\cos \left (x \right )^{2} \]

[[_3rd_order, _linear, _nonhomogeneous]]

1.022

12965

\[ {}y^{\prime \prime }-x^{2} y^{\prime }+x y = x \]

[[_2nd_order, _with_linear_symmetries]]

1.678

12966

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (x +1\right ) y = x^{2}-x -1 \]

[[_2nd_order, _with_linear_symmetries]]

1.068

12967

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 y^{\prime } x -2 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.664

12968

\[ {}\left (1-x \right ) y^{\prime \prime }+y^{\prime } x -y = \left (1-x \right )^{2} \]

[[_2nd_order, _with_linear_symmetries]]

1.587

12969

\[ {}\sin \left (x \right ) y^{\prime \prime }+2 \cos \left (x \right ) y^{\prime }+3 \sin \left (x \right ) y = {\mathrm e}^{x} \]

[[_2nd_order, _linear, _nonhomogeneous]]

8.911

12970

\[ {}y^{\prime \prime }-2 \tan \left (x \right ) y^{\prime }-\left (a^{2}+1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.599

12971

\[ {}4 x^{2} y^{\prime \prime }+4 x^{3} y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.619

12972

\[ {}x y^{\prime \prime }+2 y^{\prime }-x y = 2 \,{\mathrm e}^{x} \]

[[_2nd_order, _linear, _nonhomogeneous]]

1.829

12973

\[ {}y^{\prime \prime }+\left (2 \,{\mathrm e}^{x}-1\right ) y^{\prime }+{\mathrm e}^{2 x} y = {\mathrm e}^{4 x} \]

[[_2nd_order, _linear, _nonhomogeneous]]

1.897

12974

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-y^{\prime } x +4 y = 0 \]

[_Gegenbauer, [_2nd_order, _linear, ‘_with_symmetry_[0,F(x)]‘]]

1.422

12975

\[ {}y^{\prime \prime }+\tan \left (x \right ) y^{\prime }+\cos \left (x \right )^{2} y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

3.328

12976

\[ {}x^{6} y^{\prime \prime }+3 x^{5} y^{\prime }+y = \frac {1}{x^{2}} \]

[[_2nd_order, _linear, _nonhomogeneous]]

3.524

12977

\[ {}x y^{\prime \prime }-\left (2 x^{2}+1\right ) y^{\prime }-8 x^{3} y = 4 x^{3} {\mathrm e}^{-x^{2}} \]

[[_2nd_order, _linear, _nonhomogeneous]]

1.569

12978

\[ {}x y^{\prime \prime }-\left (x +3\right ) y^{\prime }+3 y = 0 \]

[_Laguerre]

0.940

12979

\[ {}\left (x -3\right ) y^{\prime \prime }-\left (4 x -9\right ) y^{\prime }+\left (3 x -6\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.160

12980

\[ {}x^{2} y^{\prime \prime }+4 y^{\prime } x +\left (-x^{2}+2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.254

12981

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 y^{\prime } x +2 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.152

12982

\[ {}x y^{\prime \prime }-\left (2 x -1\right ) y^{\prime }+\left (x -1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.908

12983

\[ {}x^{2} y^{\prime \prime }-4 y^{\prime } x +\left (x^{2}+6\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.480

12984

\[ {}\left (2 x^{3}-1\right ) y^{\prime \prime }-6 x^{2} y^{\prime }+6 x y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.589

12985

\[ {}x^{2} y^{\prime \prime }-2 x \left (x +1\right ) y^{\prime }+2 \left (x +1\right ) y = x^{3} \]

[[_2nd_order, _with_linear_symmetries]]

1.730

12986

\[ {}x^{2} y^{\prime \prime }-2 n x \left (x +1\right ) y^{\prime }+\left (a^{2} x^{2}+n^{2}+n \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.116

12987

\[ {}x^{4} y^{\prime \prime }+2 x^{3} \left (x +1\right ) y^{\prime }+n^{2} y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.789

12988

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = 0 \]

[[_2nd_order, _missing_y], [_2nd_order, _reducible, _mu_y_y1]]

0.728

12989

\[ {}\left (x y^{\prime \prime \prime }-y^{\prime \prime }\right )^{2} = {y^{\prime \prime \prime }}^{2}+1 \]

[[_3rd_order, _missing_y], [_3rd_order, _with_linear_symmetries]]

0.897

12990

\[ {}y^{\prime \prime }+y^{\prime } x = x \]

[[_2nd_order, _missing_y]]

1.359

12991

\[ {}y^{\prime \prime } = x \,{\mathrm e}^{x} \]

[[_2nd_order, _quadrature]]

2.002

12992

\[ {}\left (y^{\prime }-x y^{\prime \prime }\right )^{2} = 1+{y^{\prime \prime }}^{2} \]

[[_2nd_order, _missing_y]]

0.770

12993

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2}-y^{2} y^{\prime } = 0 \]

[[_2nd_order, _missing_x], [_2nd_order, _with_potential_symmetries], [_2nd_order, _reducible, _mu_xy]]

0.408

12994

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2}+1 = 0 \]

[[_2nd_order, _missing_x], [_2nd_order, _reducible, _mu_x_y1]]

2.151

12995

\[ {}2 y^{\prime \prime } = {\mathrm e}^{y} \]

[[_2nd_order, _missing_x], [_2nd_order, _reducible, _mu_x_y1]]

32.757

12996

\[ {}y y^{\prime \prime }+2 y^{\prime }-{y^{\prime }}^{2} = 0 \]

[[_2nd_order, _missing_x], [_2nd_order, _reducible, _mu_x_y1], [_2nd_order, _reducible, _mu_xy]]

0.278

12997

\[ {}\left (x^{2}-2 x +2\right ) y^{\prime \prime \prime }-x^{2} y^{\prime \prime }+2 y^{\prime } x -2 y = 0 \]

[[_3rd_order, _with_linear_symmetries]]

0.062

12998

\[ {}x y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime } x +y = -x^{2}+1 \]

[[_3rd_order, _with_linear_symmetries]]

0.061

12999

\[ {}\left (x +2\right )^{2} y^{\prime \prime \prime }+\left (x +2\right ) y^{\prime \prime }+y^{\prime } = 1 \]

[[_3rd_order, _missing_y]]

0.485

13000

\[ {}x^{2} y^{\prime \prime }+3 y^{\prime } x +y = x \]

[[_2nd_order, _exact, _linear, _nonhomogeneous]]

1.697